INTEGRASI KOMPETENSI PEDAGOGIK DAN DIGITAL GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN BERBASIS TPACK - Sayyidatul Hikmah, Naila; Hillal Hamdi, Muhammad; Ilma Nafisya , Nahdliya; Munawir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the still low digital competence of teachers and the suboptimal use of technology in learning. The study aims to analyze the integration of teachers’ pedagogical and digital competencies in improving learning quality through the Technological Pedagogical Content Knowledge (TPACK) approach. The method used is a Systematic Literature Review (SLR), examining 20 scientific articles published between 2019 and 2025 from Google Scholar and other relevant sources. Data analysis techniques include data reduction, data presentation, and systematic conclusion drawing. The findings indicate that the integration of pedagogical and digital competencies based on TPACK can enhance student interaction, motivation, and learning outcomes, particularly through the implementation of technology-based learning models such as blended learning and e-learning. The study also shows that the success of integration is influenced by teacher competence, infrastructure availability, and educational policy support. This research emphasizes that mastery of TPACK is key to transforming learning in the digital era.